Analysis of Numerical Measure and Numerical Integration Based on Measure. (12th December 2013) - Wang, Yinkun; Luo, Jianshu; Chen, Xiangling
Abstract : We present a convergence analysis for a general numerical method to estimate measure function. By combining Lagrange interpolation, we propose a specific method for approximating the measure function and analyze the convergence order. Further, we analyze the error bound of numerical measure integration and prove that the numerical measure integration can decrease the singularity for singular integrals. Numerical examples are presented to confirm the theoretical results.